Pneumococcal meningitis in Greece: A retrospective serotype surveillance study in the post-PCV13 era (2010–2020). Issue 34 (12th August 2022) - Xirogianni, Athanasia; Marmaras, Nektarios; Georgakopoulou, Theano; Papandreou, Anastasia; Simantirakis, Stelmos; Magaziotou, Ioanna; Eliades, Andreas; Getsi, Vassiliki; Anastasiou-Katsiardani, Anastasia; Staikou, Efi; Markou, Fani; Argyrοpoulou, Athina; et al.
Abstract: Background: As Greece is a country which has introduced the 13-valent pneumococcal conjugate vaccine (PCV13) both in the infant and in the adult immunization programs, the aim of the study was to investigate age-specific and serotype-specific trends of pneumococcal meningitis over an 11-year period (2010–2020). Materials and Methods: Data are reported from pneumococcal meningitis cases [notified to the National Public Health Organization (NPHO)], with clinical samples and bacterial isolates sent for pneumococcal identification and serotyping at the National Meningitis Reference Laboratory (NMRL). Pneumococcal identification was performed directly on clinical samples or bacterial isolates by multiplex PCR (mPCR) assay, while serotyping was carried out by application of the Capsular Sequence Typing (CST) method with the combination of single tube PCR assays. Results: A total of 427 pneumococcal meningitis cases were notified to the NPHO between 2010 and 2020. Among those, 405 (94.8%) were microbiologically confirmed, while samples from 273 patients were sent to the NMRL for identification and/or further typing. The annual notification rate peaked at 0.47/100, 000 in 2016 and since then has been decreasing. The incidence was highest in infants and in older adults. Pneumococcal serotypes were identified in 260/273 (95.2%) cases, where clinical samples were sent to the NMRL. The most prevalent serotypes (≥5%) were 3, 19A, 23B, 15B/C, 11A/D, 23A, 22F. During the study period there has been a decrease of PCV13 serotypes combined with an increase of non-PCV13 serotypes (p = 0.0045). Conclusions: This is the first study to report serotypes for pneumococcal meningitis across all ages in the post-PCV13 era in Greece. There is a need to enhance surveillance, by close monitoring of the emerging serotypes and the impact of vaccination programs. Higher-valency PCVs may help to improve the coverage of pneumococcal disease.